2017
DOI: 10.1021/acs.macromol.7b01827
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the Thermal Transition of β-Form Polyamide-6: Evolution of Structure and Morphology in Uniaxially Stretched Films

Abstract: Structure and morphology evolution of the uniaxially stretched polyamide-6 (PA6) film with the β-form upon heating were investigated mainly by synchrotron twodimensional (2D) wide-angle X-ray diffraction and small-angle X-ray scattering. For comparison, thermal transitions of the oriented PA6 samples with the αand γ-form were also monitored, which undergo "incomplete Brill transition" and direct melting, respectively. Using the results of oriented αand γ-PA6 as the references, we confirm that the stretched β-P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 52 publications
1
41
0
Order By: Relevance
“…The characteristic γ-PA6 diffraction peak is located at 21.3°. The single-diffraction phenomenon of PA6 is attributed to the characteristic diffraction peaks of (200) and (001) superimposed together [29]. Figure 6a shows that the characteristic peak of PEA is exactly the same as that of PA6, indicating that the crystallinity in PEA is completely determined by the polyamide 6 segment.…”
Section: Resultsmentioning
confidence: 99%
“…The characteristic γ-PA6 diffraction peak is located at 21.3°. The single-diffraction phenomenon of PA6 is attributed to the characteristic diffraction peaks of (200) and (001) superimposed together [29]. Figure 6a shows that the characteristic peak of PEA is exactly the same as that of PA6, indicating that the crystallinity in PEA is completely determined by the polyamide 6 segment.…”
Section: Resultsmentioning
confidence: 99%
“…The authors calculated the order parameter f based on the Hermans-Stein orientation distribution function. [49][50][51] Where I is the intensity and φ is the azimuthal angle as shown in Figure S2c, Supporting Information. The order parameter of aligned LCE fibers was determined to be 0.49.…”
Section: Methodsmentioning
confidence: 99%
“…A controversy exists regarding the identification of the β and γ forms of PA6 that exhibit somewhat similar X-ray scattering patterns. Indeed, it has been often reported from wide-angle X-ray scattering experiments (WAXS) that γ crystals prevail in melt spun fibers, blown and cast films, bulk crystallized samples after quick cooling, [23,[37][38][39][40][41][42][43][44][45]48,[55][56][57][58][59][60][61][62] and nanocomposites as well [32,44,[63][64][65][66][67][68][69][70][71][72][73][74] reinforced with various kinds of nanofillers. In most of these studies the γ structure has been associated to the one identified by Arimoto et al [34] on iodine-treated PA6 fibers.…”
Section: Ambiguity Between the γ Crystal Form And The β Mesophase Omentioning
confidence: 99%